A gestão do conhecimento para a promoção do desempenho organizacional : um estudo no setor de TI do Rio Grande do Sul - Junges, Fabio Miguel (Universidade do Vale do Rio dos Sinos, 2011)
Knowledge-intensive business services (KIBS) operate in the most dynamic sectors of society and involve a number of sub-sectors of the economy, including the information technology (IT). They are so classified because they have knowledge as their main raw material, and often knowledge is the end product of their operations. Knowledge management (KM) is presented here as a strategic element that can contribute to the development of these organizations, either through the generation of competitive advantage, innovation, or development of individual and organizational competencies. This research belongs to the field of organizational strategies based on resources, and it aims at identifying how KM can be structured to promote performance in organizations of knowledge-intensive services, focusing on organizations in the IT sector in RS. We proposed a conceptual model from the literature review and by conducting an exploratory stage of research, in the form of a case study in an organization in the IT market. The conceptual model suggests that KM can be one of the factors contributing to organizational performance, and that its effects can be perceived on three dimensions of business: external business relationships, internal structures and relationships, and competence in innovation. We conducted a survey in order to verify this model empirically, and we consolidated a database with 811 organizations in the IT sector of the RS. A scale was created and validated specifically for the purposes of this survey, whose final stage of data collection was completed with a sample of 222 respondents. We have used the statistical technique of structural equation modeling (SEM), and tests have validated the conceptual model and confirmed the research hypotheses set. The results indicate that KM is a factor in promoting the performance of service organizations in knowledge-intensive, and that its effects can be observed from the three business set. The following have stood out as the enablers for the development of KM: culture, information technology, organizational structure, and focus on skill development. We also concluded that the empirical studies relating KM with organizational performance are still incipient, specially those investigating this relationship in small and medium organizations. Therefore, we suggest further studies to advance the understanding of the elements related to KM that can promote the generation of competitive advantage and superior performance.
Keywords: Gestão do conhecimento; KIBS; Vantagem competitiva; Tecnologia da informação.; Knowledge management; Competitive advantage; Information technology; ACCNPQ::Ciências Sociais Aplicadas::Administração